The Influence of Working Capital on MSME Sustainability with Liquidity Level as a Mediator - Gregorius Paulus Tahu; Yenny Verawati; Dominicus Djoko Budi Susilo (Borong Newinera Publisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a crucial pillar of Indonesia's economy, significantly contributing to the national GDP and absorbing the majority of the workforce. However, MSMEs face various challenges, particularly related to limited working capital and liquidity issues, which can threaten their business continuity. This study aims to analyze the impact of working capital on the sustainability of MSMEs, as well as the role of liquidity as a mediator in this relationship. Additionally, the study explores external factors, such as government policies and market changes, that influence MSME sustainability. Using a literature review method, this research examines previous studies on working capital management, liquidity, and external factors that support MSME sustainability. The findings indicate that well-managed working capital facilitates operations and enhances MSME competitiveness, while adequate liquidity functions as a crucial link ensuring business continuity. External factors, such as government policies, also play a significant role in creating an ecosystem that supports MSME growth. Therefore, this study suggests that MSMEs optimize their working capital management, improve financial literacy, and leverage financial technology to maintain business continuity. Furthermore, adequate policy support is essential to create a conducive environment for MSMEs.